Correlación entre teorías constitucionales y métodos de interpretación: la eutanasia como caso de estudio en Colombia. - Mondragón Duarte, Sergio Luis; Guzmán Quintero, Aldemar; Franco Mateus, Laura Marcela; Sánchez Rengifo, Sergio Luis (Revista Pensamiento Americano)
Introduction: The text addresses the relationship between constitutional theories and methods of interpretation, using euthanasia in non-terminal illnesses in Colombia as a case study. Objective: Determine the relationship between constitutional theories and interpretation methods in the context of euthanasia, highlighting the change in Colombian jurisprudence in 2020. Reflection: The application of interpretation methods by the Constitutional Court in specific cases, such as Martha Liria, is evident. Sepúlveda and Víctor Julio Escobar, based on the analysis made in this regard from constitutional theories, such as the original, customary law, judicial activism and approaches of authors such as Dworkin, Alexy, Habermas and Nino. Which results in generating an impact on the fundamental guidelines and principles for constitutional interpretation, as well as different types of interpretation, such as authentic, doctrinal and judicial. Conclusion: The importance of having interpretation methods to guarantee rights in modern States is highlighted, highlighting the complexity and dynamism of the constitutional interpretation process, making it pertinent to establish a more deep-rooted connection between constitutional theories and interpretation techniques in the context of euthanasia in Colombia, analyzing specific cases and providing data on its practice in the country.